Kant, republicanism and civil society - Caviglia, Alessandro (2019)
This paper presents how republicanism from civil society allows a critique of the phenomena present in contemporary societies, especially forms of despotism that are based on dogmatisms and fundamentalisms. To that end, he begins by presenting the way in which Hume and Rousseau's thoughts are used by Kant to articulate a republican conception. Next, he goes on to see how this conception allows criticism of contemporary civil society.